2006
DOI: 10.1530/rep.1.01148
|View full text |Cite
|
Sign up to set email alerts
|

Expression of stathmin in human uterus and decidualizing endometrial stromal cells

Abstract: The cytosolic phosphoprotein stathmin is upregulated at the site of embryo implantation in the rodents. However, stathmin expression in the human uterus has not yet been investigated. The distribution of uterine and placental stathmin was analyzed by immunohistochemistry, while stathmin mRNA expression was detected in endometrial tissues by the reverse transcriptase-PCR. Cultured endometrial stromal cells were used to investigate whether stathmin plays a role in decidualization. Stathmin is expressed specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
(46 reference statements)
3
12
0
Order By: Relevance
“…Stathmin silencing in primary stromal cells using small interfering RNA before the cells are exposed to decidualizing agents also markedly suppresses decidualization, suggesting that stathmin may play a key role in decidualization. 6 Stathmin overexpression favors microtubule destabilization, whereas decreased stathmin expression favors elongated, bundled microtubules and an increased ratio of polymerized to soluble tubulin. 23 Immunohistochemical analyses using a rat model previously revealed that stathmin-1 is exclusively localized in decidual cells, especially in the primary decidual zone surrounding the embryo with markedly more intense staining on day E9.5 than on day E7.5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stathmin silencing in primary stromal cells using small interfering RNA before the cells are exposed to decidualizing agents also markedly suppresses decidualization, suggesting that stathmin may play a key role in decidualization. 6 Stathmin overexpression favors microtubule destabilization, whereas decreased stathmin expression favors elongated, bundled microtubules and an increased ratio of polymerized to soluble tubulin. 23 Immunohistochemical analyses using a rat model previously revealed that stathmin-1 is exclusively localized in decidual cells, especially in the primary decidual zone surrounding the embryo with markedly more intense staining on day E9.5 than on day E7.5.…”
Section: Discussionmentioning
confidence: 99%
“…6 When stromal cells isolated from normal endometrial tissues were previously cultured and stimulated to decidualize by progesterone plus estrogen or cAMP, their total and phosphorylated stathmin levels decreased. Stathmin silencing in primary stromal cells using small interfering RNA before the cells are exposed to decidualizing agents also markedly suppresses decidualization, suggesting that stathmin may play a key role in decidualization.…”
Section: Discussionmentioning
confidence: 99%
“…After 6 days of culture in culture medium containing 2% FBS, these cells exhibited a spindle-shaped morphology (Fig. 1A, control), which is similar to primary stromal cells [16]. To determine whether EtsT cells retain the characteristis of primary endometrial stromal cells, we examined their ability to decidualize upon stimulation with forskolin (an activator of protein kinase A) or the cAMP analog db-cAMP.…”
Section: Ability Of Db-camp or Forskolin To Induce Etst Decidualizationmentioning
confidence: 89%
“…Endometrial stromal cells were prepared from the endometrial tissues of patients undergoing surgery or biopsies, as described previously [16]. Sample collection was conducted with the informed consent of the patients in accordance with the requirements of the clinical research ethics committee of the Tokyo Medical University Hospital.…”
Section: Tissue Collection and Immortalization Of Endometrial Stromalmentioning
confidence: 99%
See 1 more Smart Citation